MEN’S VIEW ON WOMEN’S INDEPENDENCE IN ANDY FICKMAN’S MOVIE SHE IS THE MAN - Artificianti, Khairunnisa (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2012)
This final project tells about Men’s View on Women’s Independence which is found in the movie She is the Man. The main reason for choosing the topic is to prove that people can get moral education by studying literature. Film, as an imaginative literary work has so many characters with various kinds of experiences and behaviors. I used a descriptive qualitative as a method of this study since the data are in the form of written words and they were descriptively analyzed. There were several steps in analyzing this study. First of all I watched the movie and read the dialogues in the movie several times in order to understand the whole content of the movie. Secondly, I listed the data that are related to the topic and then categorized them. The next step was interpreting the data according to the theory related to the topic to interpret and analyze the meaning. From the analysis, I found out that there are various characteristics of men’s view on women’s independence that reflected in the female life nowadays. In addition, we can also find the causes of this syndrome so that we are able to propose solutions of the syndrome itself.